Analisis In Vivo Aktivitas Antihipertensi dari Protein Biji Melinjo (Gnetum gnemon) Terhidrolisis - Yeni Tri Puspitaningrum; Erfan Efendi; Tri Agus Siswoyo (UPT Percetakan dan Penerbitan Universitas Jember, 2014)
Hypertension is a serious health problem and requires a good handling. An alternative treatment for hypertension is required due to the treatment of hypertension took a long period of time causing unwanted side effects. Melinjo seed hydrolyzed-proteins have an ACE-inhibitor activity, an antihypertensive effect. This study aimed to determine the antihypertensive effects of melinjo seed hydrolyzed-proteins in hypertensive rats. Wistar rats induced with prednisone 1,5 mg/kg body weight and 2% NaCl for 7 days and then treated. There were 7 groups: a normal group K, a group K(-) which is a hypertensive rats without treatment, a group K(+) which is hypertensive rats with captopril 2,5 mg/kg body weight on day 8th, and four treatment groups P1, P2, P3, and P4 which are hypertensive rats with melinjo seed hydrolyzed-proteins with a dose of 5, 10, 20, and 30 mg/kg body weight on day 8th, respectively. Blood pressure was measured before and after treatment every 1 hour for 5 hours. The results showed that melinjo seed (Gnetum gnemon) hydrolyzed-proteins can decrease blood pressure in hypertensive rats. Keywords: Antihypertensive, Gnetum gnemon, Hydrolized-Protein, Blood Pressure